Seasonality in terminus ablation rates for the glaciers in Greenland (Kalaallit Nunaat) - A. KC; E. M. Enderlin; D. Fahrner; T. Moon; D. Carroll; D. Carroll (The Cryosphere)
Marine-terminating glaciers of Greenland (Kalaallit Nunaat) have been losing mass since the 1990s, with a substantial portion caused by the effects of dynamic change. Conventional assessments of dynamic mass loss, however, often ignore the influence of terminus advance or retreat on the timing of mass loss. Here, we construct and analyze a decade (2013–2023) of monthly ice flux driven both by temporal variability in ice flow (i.e., discharge) and terminus position change – collectively called terminus ablation – for 49 marine-terminating glaciers in Greenland. We calculate terminus ablation rates using open-source datasets, including terminus position, ice surface elevation, ice thickness, and glacier speed. For the majority of glaciers, we observe coincident seasonal variations in terminus position and discharge. However, seasonal variations in terminus ablation are much larger than those in discharge. For the northwest and central west sectors, where the highest fractions of outlet glaciers are included in our terminus ablation dataset, terminus ablation varies by ∼ 51 and ∼ 25 Gt yr−1, respectively, over each year. In contrast, the corresponding variation in discharge is only ∼ 5 Gt yr−1. While our terminus ablation time series do not include every outlet glacier, they suggest that terminus position change is the dominant contributor to Greenland glacier dynamic mass loss at seasonal timescales, in contrast with the relatively small influence of terminus change on decadal-scale mass loss. Since seasonality in mass loss can influence the fate of freshwater fluxes, we recommend that studies concerned with the impacts of Greenland mass loss on local to global ocean properties should account for seasonal terminus position change.